By object or by effect? The collusive potential of first refusal contracts - Patrick Van Cayseele; Andreas Bovin (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2022)
This article examines the collusive potential of first refusal contracts, which are contracts that grant one party, the buyer, a right of first refusal on the output of another party, the seller. When two parties enter into this type of contract, the seller is obligated to offer any output she wishes to sell to the buyer first. It is only after a 'first refusal' by the buyer that output can be offered to third parties. We compare the outcomes which arise under first refusal contracts with those resulting from explicit cooperation. Our findings suggest that these contracts can result in an identical distortion of competition, while remaining under the radar of antitrust authorities.
Keywords: L4; L40; L41; L42; 330; Right of first refusal; contracts; theory of harm; abuse of bargaining power